2022
DOI: 10.1186/s12969-022-00741-3
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile diabetes and systemic sclerosis: just a coincidence?

Abstract: Background Limited joint mobility (LJM), previously known as cheiroarthropathy, refers to the presence of reduced extension at the finger joints in people with diabetes and may be associated with scleroderma-like syndromes such as diabetic sclerodactyly. While scleroderma-like syndromes and LJM have been observed in patients with long-term diabetes and associated complications, the coexistence of diabetes with Juvenile systemic sclerosis (jSSc) is rarely described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…One study reported the coexistence of T1D and SSc when a 14-year-old T1D patient was found to have developed SSc upon the diagnosis of cheiroarthropathy, which is characterized by the thickening of dorsal and palmar surfaces of the skin due to long-standing uncontrolled diabetes [26]. Positive autoantibodies, aberrant nailfold capillaroscopy with scleroderma patterns, interstitial lung disease, and cardiac involvement were all detected after a thorough work-up of the case, which confirmed the diagnosis of SSc in the patient [27][28][29]. On the other hand, T H17 cells and IL-17 molecules were found to be involved in the pathogenesis of both PSR and SSc [30,31].…”
Section: Approximation Of Scale-free Networkmentioning
confidence: 58%
“…One study reported the coexistence of T1D and SSc when a 14-year-old T1D patient was found to have developed SSc upon the diagnosis of cheiroarthropathy, which is characterized by the thickening of dorsal and palmar surfaces of the skin due to long-standing uncontrolled diabetes [26]. Positive autoantibodies, aberrant nailfold capillaroscopy with scleroderma patterns, interstitial lung disease, and cardiac involvement were all detected after a thorough work-up of the case, which confirmed the diagnosis of SSc in the patient [27][28][29]. On the other hand, T H17 cells and IL-17 molecules were found to be involved in the pathogenesis of both PSR and SSc [30,31].…”
Section: Approximation Of Scale-free Networkmentioning
confidence: 58%